A REVIEW ON GREEN PRACTICES IN HOTEL INDUSTRY - Norazlina Rahmat; Muhammad Aiman Aisy Mohd Daud; Norzaidah Ngali; Muhammad Khairul Nizam Abdullah (International Journal of Accounting, Finance and Business, 2022)
Green hotel practices are efforts or changes to hotel operations that give hotels withadvantages and benefits if embraced. The goal of this study is to identify studies on green hotelpractices. A review approach is applied, and 38 out of 219 studies meet the search criteria.From that number,18 of those studies focusses on hotel green practices motivators. Based onthe analysis of the studies, four factors motivate hotel organizations to apply green practices:competition, cost savings, growth, and the environment. International and domestic theoreticalcontributions from 2010 to 2022 are used in this study. The review discusses the benefits anddrawbacks of green hotel policies. The findings may help the hotel industry promote moresustainable and environment practices. Finally, this study will be a helpful resource forcompanies looking to learn about environmentally friendly hotel management while alsoattempting to implement green marketing strategies.